Think like a startup get agile and unleash your inner entrepreneur - Sammartino, Steve (Be your best., 2020)
Reboot your entrepreneurial spirit and excel in the digital age The days of being locked into a single career for life are long gone. It's time to reinvent yourself, transform your life and work the new economy for everything it's worth. With the industrial age quickly vanishing in the rearview mirror, Think Like a Startup is your instruction manual for hacking your mind and acquiring the skills to take control of your life and fortunes in the digital age. Inspirational, subversive, and with a wealth of insightful guidance, Think Like a Startup will help you to break from a lifetime of legacy programming and take full advantage of the technology revolution.